2016
DOI: 10.1074/jbc.m116.749697
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and Extra-terminal (BET) Protein Inhibitors Suppress Chondrocyte Differentiation and Restrain Bone Growth

Abstract: Edited by Xiao-Fan WangSmall molecule inhibitors for bromodomain and extra-terminal (BET) proteins have recently emerged as potential therapeutic agents in clinical trials for various cancers. However, to date, it is unknown whether these inhibitors have side effects on bone structures. Here, we report that inhibition of BET bromodomain proteins may suppress chondrocyte differentiation and restrain bone growth. We generated a luciferase reporter system using the chondrogenic cell line ATDC5 in which the lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The proteins that “read” the histone PTMs are also important for cell differentiation. Proteins from the bromodomain and extra‐terminal domain (BET) family recognize and bind to acetylated lysine on histones, forming a scaffold for protein complexes involved in gene transcription . The inhibition of BET proteins leads to a suppression of osteoclast differentiation and activity in vitro .…”
Section: Histones and Chromatin Structure In Skeletal Disordersmentioning
confidence: 99%
“…The proteins that “read” the histone PTMs are also important for cell differentiation. Proteins from the bromodomain and extra‐terminal domain (BET) family recognize and bind to acetylated lysine on histones, forming a scaffold for protein complexes involved in gene transcription . The inhibition of BET proteins leads to a suppression of osteoclast differentiation and activity in vitro .…”
Section: Histones and Chromatin Structure In Skeletal Disordersmentioning
confidence: 99%
“…In these experiments, CPI203 prevented BMSC‐mediated protection from the cytotoxic effects of the drug as well as the increased proliferation of MM cells usually found in BMSC cocultures. Interestingly, BETi suppressed chondrocyte differentiation in vitro and reduced bone growth in vivo in a zebra fish model . BRD4 binds to and upregulates expression of OB‐specific enhancers and matrix‐specific genes during lineage commitment during OB differentiation.…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 99%
“…It may because of different sources of the chondrocytes in two studies. The chondrocytes in our study were achieved from OA patients who underwent knee replacement surgery, and the chondrocytes in the previous study were achieved from newborn mouse [ 15 ]. Our result suggested that repression of SOX9 contributed to the regulation of I-BET151 on the expression of matrix genes of chondrocytes, but other mechanisms might also occur in this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that inhibiting BET led to repression of ACAN and COL2A1 in chondrocytes; it may be another reason for the attenuation of protecting effect at 8 weeks after treatment. The previous report stated that inhibiting BET can restrain bone growth, and there have been some reports indicated the importance of subchondral bone remodeling in etiology of OA [ 15 , 28 , 29 ], so the effect on subchondral bone by inhibiting BET might affect OA progress and needed further evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation